Consideration of Liver Function test with Erythropoietin Hormone Levels in Iraqi Patients Diagnosed with Lymphoid and Myeloid Leukemia - Rezaieg, Nour Sh (Iraqi Journal of Cancer and Medical Genetics, 2018)
The study was carried out to measure the erythropoietin hormone level and a number of the hematological variables (redblood cells, platelets, monocytes and lymphocytes) and biochemical variables (erythropoietin, alkaline phosphatase, alaninetransaminase and aspartate transaminase) for two types of leukemia (lymphoid leukemia and myeloid leukemia). EnzymeLinked Immune Sorbent Assay (ELISA) was used to detect level of erythropoietin in patients with lymphoid and myeloid,leukemia and control group , liver enzymes activity were measured including alkaline phosphatase (ALP) alanine transaminase(ALT) and aspartate transaminase (AST). Also estimated some hematological variables were estimated: red blood cells,platelets, lymphocytes and monocytes, as well as, ABO blood groups in all studied groups. The statistical analysis showedsignificant (P< 0.05) increase in the level of erythropoietin, liver enzymes, lymphocytes and monocytes number in patientswith lymphoid and myeloid leukemia when compared with the control group. While, there was a decrease (P< 0.05) in redblood cells count and platelets count in the patients groups compared with the healthy group. Also, the results from statisticalanalysis revealed that there was a strong correlation between ABO blood groups and leukemia.